On the classification of non-heart-beating donors - M. Sh. Khubutia; V. L. Vinogradov; V. A. Gulyaev; A. V. Prokudin (Трансплантология (Москва))
In this report 43 donor cards of potential and actual non-heart-beating donors for 2008–2011 were retrospectively examined. It was noted that 15 donors did not match any of known categories in accordance with the Maastriht classification. In the analysis of this group of donors, it was found that all of them had clinical signs of brain death, but because of the impossibility of maintaining of «Instructions for stating a person's death on the basis of the diagnosis of brain death», a complete diagnosis of brain death, namely, performing the test of apnoetic oxygenation (separating test) was not possible. Removal of organs from these donors was carried out after the diagnosis of biological death only. The authors offer to supplement the Maastriht classification of non-heart-beating donors with a new category – the category VII (partially controlled donors).